Informe de auditoría según la NIA 700, caso dictamen con salvedad. - Cuenca Sares, Darwin Eduardo (My University, 2022)
The financial audit focuses its study on the analysis of the Financial Statements of the audited company, in order to detect errors for the application of corrective measures to in turn make the necessary adjustments and the presentation of reasonable balances in their reports, with which managers can make the right decisions. In this sense, the main objective of the case is to prepare the audit report through the application of NIA 700 for the issuance of the respective auditor's opinion, for which the investigation in the Property, Plant and Equipment component was emphasized. To resolve the aforementioned objective, an analytical-descriptive methodology was used, which allows the support of the case in reliable sources, and the detailed description of the process to be followed for its resolution. Thanks to what was stated in previous lines, it was possible to obtain as a result the audit report regarding the classification of the asset accounts and their due adjustments on their depreciation, which gives the auditor sufficient grounds to issue an opinion with exception, since the error presented has not been the subject of a relevant materiality for the company. Finally concluding that the preparation of the audit report in accordance with the respective standard, gives managers sufficient information on the way in which the company has operated in a given time, therefore the implementation of audits is a determining factor in organizational growth.
La auditoría financiera enfoca su estudio en el análisis de los Estados Financieros de la empresa auditada, con la finalidad de detectar errores para la aplicación de medidas correctivas para a su vez realizar los ajustes necesarios y la presentación de saldos razonables en sus informes, con los cuales los directivos puedan tomar decisiones acertadas. En tal sentido se establece como objetivo principal del caso elaborar el informe de auditoría a través de la aplicación de la NIA 700 para la emisión del respectivo dictamen del auditor, para ello se enfatizó la investigación en el componente Propiedad, Planta y Equipo. Para dar resolución al objetivo antes mencionado, se empleó una metodología de carácter análitico-descriptivo, lo que permite la sustentación del caso en fuentes fidedignas, y la descripción detallada del proceso a seguir para su resolución. Gracias a lo expuesto en líneas anteriores, se pudo obtener como resultado el informe de auditoría en cuanto a la clasificación de las cuentas de activos y sus debidos ajustes sobre la depreciación de los mismos, lo que da al auditor fundamento suficiente para emitir una opinión con salvedad, por cuanto el error presentado no ha sido objeto de una materialidad relevante para la empresa. Concluyendo finalmente que, la elaboración del informe de auditoría en apego a la respectiva norma, da a los directivos la información suficiente sobre la forma en la que la empresa ha operado en un determinado tiempo, por ello la implementación de auditorías es un factor determinante en el crecimiento organizacional.
Keywords: AUDITORÍA FINANCIERA; OPINIÓN AUDITOR; NIA; HALLAZGO